The factors associated with Zakat compliance behaviour among employees - Sheikh Mokhtar, Siti Salwa; Bali Mahomed, Anuar Shah; Hashim, Haslinda (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
This research attempts to understand the factors associated with Zakat income compliance behaviour among employees in Melaka, Malaysia. It is argued that the number of Muslims living in poverty is growing faster than the number of Zakat payers which reflect the low compliance towards the act of paying Zakat among Muslims. Thus, this study seeks to understand the religious practice and attitude of the Zakat payers that influence their willingness to comply towards the behaviour of paying Zakat. This study provides the theoretical insight by combining the element in Theory of Reasoned Action (1980) and the measurement of Muslim Religiosity-Personality Inventory (2005) in a single model which provides multidimensional findings in Zakat compliance behaviour. Data from 217 respondents were recorded and the respondents were consisted of public and private sectors‟ employees. The data were then analysed using SPSS. The existing variable; attitude, subjective norm and religiosity were found to be statistically significant on Zakat compliance behaviour. The implications of this study will enhance the Zakat institution to increase the Zakat collection in the future and to improve the institutional way by focusing on specific target group to increase the voluntary behaviour in order for the members to pay Zakat. It may also helps in developing an extensive way of understanding the individual’s behaviour on complying towards the act of Zakat and empowering the community development in Malaysia.